Lutter contre l'extrème droite. - Humbert-Lindeperg, Michèle; Dufour, Claire; Ghayet, Ahmed; Guillot, Didier; Guittonneau, Claudine; Petit, Eric (Paris : Parti Socialiste de France, 1990)
Sevi
Frans
Monografie